Prevalence and Incidence of Multiple Myeloma in Urban Area in China: A National Population-Based Analysis - Wang, Shengfeng; Xu, Lu; Feng, Jingnan; Liu, Yang; Liu, Lili; Wang, Jinxi; Liu, Jack; Huang, Xiaojun; Gao, Pei; Lu, Jin; Zhan, Siyan (Frontiers in Oncology, 2020)
Multiple myeloma (MM) is the second most frequent malignancy of blood and information on disease burden of MM was limited in developing countries. We aimed to estimate the prevalence and incidence of MM in China. We used data from the national urban employee and urban resident basic medical insurance from 2012 to 2016 in China. MM cases were based on the primary diagnose (ICD code, ICD for Oncology, or text of diagnosis) of patients. The crude prevalence and incidence were 6.88 per 100 000 population (95% CI, 5.75 to 8.00) and 1.60 (1.28 to 1.92), respectively. The standardized prevalence and incidence were 5.68 (5.64 to 5.72) and 1.15 (1.11 to 1.19), respectively. Overall, the rates were higher in males compared with females for prevalence (6.77 versus 5.18, P<0.05) and incidence (1.41 versus 1.02, P<0.05). Both rates increased with age, and the mean age (SD) of MM patients were 57.9 (14.4) years. Prevalence peaked between 55 and 74 years old for both genders. The incidence in women aged 55-59 had significantly high incidence of 5.53(4.98 to 6.11). The prevalence and incidence were significantly lower than those in North America, Australia, and Western Europe, but were in the same range as those in Japan or Korea. MM should be one of the cancers in the spotlight from both medical and socioeconomic perspectives in low-resource but populous countries because of the appearing of more elderly MM patients in next decade. Further research is warranted to examine potential pathophysiologic mechanism.